2021
DOI: 10.3390/molecules26154566
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity and Mechanism Investigation of Hypericin as a Novel α-Glucosidase Inhibitor

Abstract: α-glucosidase is a major enzyme that is involved in starch digestion and type 2 diabetes mellitus. In this study, the inhibition of hypericin by α-glucosidase and its mechanism were firstly investigated using enzyme kinetics analysis, real-time interaction analysis between hypericin and α-glucosidase by surface plasmon resonance (SPR), and molecular docking simulation. The results showed that hypericin was a high potential reversible and competitive α-glucosidase inhibitor, with a maximum half inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Another compound that has been studied due to its potential anticancer properties [ 61 ] is hypericin, a polycyclic aromatic naphthodianthrone that occurs naturally. It has been previously shown that hypericin induced cell death of human and bovine isolated RPE cells [ 62 , 63 ].…”
Section: Natural Productsmentioning
confidence: 99%
“…Another compound that has been studied due to its potential anticancer properties [ 61 ] is hypericin, a polycyclic aromatic naphthodianthrone that occurs naturally. It has been previously shown that hypericin induced cell death of human and bovine isolated RPE cells [ 62 , 63 ].…”
Section: Natural Productsmentioning
confidence: 99%
“…Further, hypericin and other bioactive components in the extract from Hypericum humifusum may inhibit acetylcholinesterase and some key enzymes linked to T2D, or downregulate homeobox‐1 (PDX1) expression and Erk activity 87,88 . In addition, hypericin is found to be an effective inhibitor of α‐glucosidase, a major enzyme that is involved in T2D, by altering its structure and microenvironment and reducing its activity 89 …”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Hyp suppressed islet β‐cell apoptosis and improved the antioxidative ability of pancreatic tissue, thus ameliorating the function of islet β‐cell. Besides the protective effect on islet β‐cell both in vitro and in vivo, Dong, Hu, et al (2021) found the binding affinities of Hyp with α‐glucosidase were strong and fast, with a maximum IC50 of 4.66 ± 0.27 mg/L. Moreover, hydrogen bonding occurred between Hyp and α‐glucosidase amino acid residues Lys‐156, Ser‐157, Gly‐160, Ser‐240, His‐280, Asp‐242, and Asp‐307, revealing that Hyp could be applied as a novel α‐glucosidase inhibitor to treat diabetes.…”
Section: Pharmacological Effects Of Hypericinmentioning
confidence: 99%